2022
DOI: 10.3389/fsufs.2022.836275
|View full text |Cite
|
Sign up to set email alerts
|

Successful Co-Feeding of Asian Seabass, Lates calcarifer Larvae With Palm Oil-Based Microdiets and Live Feeds

Abstract: Palm oil has been recognized as a high potential alternative dietary lipid source to reduce the reliance on expensive fish oil in aquaculture feeds. Unfortunately, most research studies were focusing on the juvenile or grow-out stage of aquatic species. This study was designed to develop weaning microdiets for Asian seabass larvae with dietary fish oil being replaced with crude palm oil (CPO) at 25, 50, and 75% (CPO25, CPO50, and CPO75) and refined bleached deodorized palm olein, refined palm oil (RPO) at 50 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Red snapper and Asian seabass are the key cultured food fishes in Singapore [ 2 , 3 , 4 ]. Farmed red snappers are usually offered pelleted feeds containing more than 40% protein, compared to 45–55% in the feeds of Asian seabass [ 5 ]. An analysis of fillet fatty acid profiles by Durmus [ 6 ] revealed that all 13 seafood species studied had elevated levels of eicosapentaenoic acid (EPA, C20:5n-3) and docosahexaenoic acid (DHA, C22:6n-3) and had higher levels of Σn-3 poly unsaturated fatty acids (PUFAs) than Σn-6 PUFAs, underscoring the nutritional value of seafood.…”
Section: Introductionmentioning
confidence: 99%
“…Red snapper and Asian seabass are the key cultured food fishes in Singapore [ 2 , 3 , 4 ]. Farmed red snappers are usually offered pelleted feeds containing more than 40% protein, compared to 45–55% in the feeds of Asian seabass [ 5 ]. An analysis of fillet fatty acid profiles by Durmus [ 6 ] revealed that all 13 seafood species studied had elevated levels of eicosapentaenoic acid (EPA, C20:5n-3) and docosahexaenoic acid (DHA, C22:6n-3) and had higher levels of Σn-3 poly unsaturated fatty acids (PUFAs) than Σn-6 PUFAs, underscoring the nutritional value of seafood.…”
Section: Introductionmentioning
confidence: 99%